PENGGUNAAN METODE QUESTION STUDENT HAVE DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Fathor Rozi; Fajri, Zaenol; Intan Nuraini, Yulia Putri (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Student learning activity in general is a student who is involved in the process of teaching and learning activities, such as finding the main idea of ​​subject matter, solving problems or applying what students learn to a problem that exists in real life. In increasing activeness in learning, there needs to be a teacher factor, where this factor is the most important in the learning process, in essence the teacher is the one who directly facilitates the learning process. Because activeness in learning greatly influences learning outcomes or achievements with students being active in the classroom, actively asking questions, actively answering teacher questions, writing, listening and so on. The research aims to determine the use of the Student Have Question Method in increasing student learning activity. This research uses a qualitative method with a case study type, the case study type was chosen to explore data, explain facts, understand and explain phenomena and events that occur at an object located at MTs Miftahul Khair. The use of this type of research method is carried out within an integrated framework. The results of this field research found that the implementation of the Question Student Have method at MTs Miftahul Khair positively increased student participation, opened up opportunities for developing critical thinking skills, and had a positive impact on student memory and understanding. This method succeeds in creating a more interactive learning environment and supports holistic student growth. The implications of using the Question Student Have Method encourage students to ask questions, and can increase student involvement in the learning process. Students who actively ask questions tend to be more mentally and emotionally involved in the learning material